PETA DIGITAL KOTA BITUNG - Kaunang, Sumenge; Lumenta, Arie; Ratu, Ferouw R I (Jurnal Teknik Informatika, 2013)
AbstractInternet as a medium for exchange of information globally continues to grow rapidly. These developments include aspects of technology in developing Geographic Information System. With the emergence of what is termed as WebGIS, the Geographic Information System based on the Internet that makes GIS can be accessed from anywhere. We have also occurred changes in the pattern of web-based information systems, where users not only as consumers, but can become producers and distributors. This system is a new option for application developers to create a more interactive GIS with various features and facilities therein. GIS also has become a substitute for Conventional maps that have existed since long, so GIS can also be referred to as the Digital Map. Digital maps can minimize shortages Conventional Map fragile and inflexible. Bitung City Digital Map is designed to respond to the needs of geographic information the community needs of Bitung City. Objects that appear in this system of Government Office, Object Tourism and Public Facilities. This system uses Apache as the web server and TimeMap as the map server.Keywords: Digital Map, Geographic Information System, WebGIS